Manipulating Ghanaian indigenous vegetable tanned leather for the production of ladies fashionable accessories - Andoh, Rita Dora (2016)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of the Degree of Master of Philosophy in Integrated Art (Leather Technology), 2015